Organization and Chromosomal Distribution of Histone Genes and Transposable Rex Elements in the Genome of Astyanax bockmanni (Teleostei, Characiformes) - Daniel, Sandro N. [UNESP]; Penitente, Manolo [UNESP]; Silva, Duílio M.Z.A. [UNESP]; Hashimoto, Diogo T. [UNESP]; Ferreira, Daniela C.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Karger Publishers, 2015)
An important feature of eukaryotic organisms is the number of different repetitive DNA sequences in their genome, a feature not observed in prokaryotes. These sequences are considered to be important components for understanding evolutionary mechanisms and the karyotypic differentiation processes. Thus, we aimed to physically map the histone genes and transposable elements of the Rex family in 6 fish populations of Astyanax bockmanni. FISH results using a histone H1 gene probe showed fluorescent clusters in 2 chromosome pairs in all 6 samples analyzed. In contrast, FISH with a histone H3 probe showed conspicuous blocks in 4 chromosomes in 5 of the 6 populations analyzed. The sixth population revealed 7 chromosomes marked with this probe. Probes for the transposable elements Rex1 and Rex6 showed small sites dispersed on most chromosomes of the 6 populations, and the Rex3 element is located in a big block concentrated in only 1 acrocentric chromosome of 2 populations. As for the other populations, a Rex3 probe showed large blocks in more than 1 chromosome. Fish from Alambari and Campo Novo Stream have Rex3 elements dispersed along most of the chromosomes. Additionally, the conspicuous signals of Rex1, Rex3, and Rex6 were identified in the acrocentric B microchromosome of A. bockmanni found only in individuals of the Alambari River. Thus, we believe that different mechanisms drive the spread of repetitive sequences among the populations analyzed, which appear to be organized differently in the genome of A. bockmanni. The presence of transposable elements in the B chromosome also suggests that these sequences could play a role in the origin and maintenance of the supernumerary element in the genome of this species.
Keywords: Histone genes; Neotropical fish; Repetitive DNA; Transposable Rex elements